PENANGANAN PASCA PANEN PADI DI INDONESIA - Sutrisno Sutrisno (PERTETA, 2007)
ABSTRACT Post-harvest technology is a general terminology of various process technologies needed to minimize losses of product during the processes after harvest. As a staple food of most of Indonesian people, rice has an important role in Indonesian food security. Although the production becomes close to the national demand, due to the fluctuation of production caused by unstable weather, the problem on rice is still faced from year to year. Especially in the post-harvest area, recently the problem on quantity and quality losses still remains high. This paper discusses about the problem on post-harvest handling of rice in Indonesia, and how to reduce the post-harvest losses, and what are the critical parameters during post-harvest handling of rice. Diterima:10 Mei 2007, Disetujui:. 22 Mei 2007